THE EXPERIENCE OF TRAINING EXPERTS IN THE FIELD OF EDUCATION IN EASTERN EUOROPE - Ilona Tryhub (Borys Grinchenko Kyiv Metropolitan University, 2019)
In the article has been singled out features of the classification of Eastern Europe countries according to the professional training of experts in the field of education (systematicity and length of training); founded the tendencies of professional training of experts in the field of education in countries of Eastern Europe: general tendencies (in particular: orientation of training of experts in the field of education in quality assurance; implementation of professional training of experts in the field of education in masters training, postgraduate education and non-governmental organizations; the introduction of seminars, workshops and conferences as forms of training of experts in the field of education; election of future experts in the field of education among experienced teachers; election of candidates are offered by universities, rectors conferences, schools and universities, students parliaments, national academic associations and employers' organizations; implementation of the official Code of Ethics in professional activities of experts in the field of education; introduction of state and public control over the activity of experts in the field of education; exchange of experience of expert activity in the international cooperation); specific tendencies (in particular: entrance examination / briefing by experts in the field of education (the Republic of Lithuania); preparation of experts in the field of education at the level of the master's degree in higher educational institutions (the Republic of Latvia); professional training of experts in the field of education in different forms (seminars, advanced training courses, postgraduate studies) (Russian Federation) etc